Nationalism, Islam and Marxism. Transl. by K.H. Warouw and P.D. Weldon. With an introd. by R.T. McVey (Southeast Asia Program, Department of Asian Studies, Cornell University, 1970)
Translation series. Modern Indonesia project. Stencil.